Lithium-rich manganese-based material for all-solid-state battery as well as preparation method and application of lithium-rich manganese-based material

By using lithium-rich manganese-based positive electrode materials with doped rare earth ions and designed submicron single crystal structures in all-solid-state lithium-ion batteries, and using in-situ coating to construct fast ion conductor cladding, the problems of slow kinetics and interfacial side reactions are solved, and higher energy density and cycle life are achieved.

CN119706967APending Publication Date: 2025-03-28JINGMEN GEM NEW MATERIAL CO LTD +1

Patent Information

Application Number
CN202411906058.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The lithium-rich manganese-based positive electrode material in all-solid-state lithium-ion batteries has problems of slow kinetics and severe interface side reactions, which limits its energy density, safety and cycle life.

Method used

By doping rare earth ions in the lithium-rich manganese-based carbonate precursor, a submicron single crystal structure is designed, and a fast ion conductor cladding layer is constructed by in-situ coating method to improve the lithium ion migration speed and interface stability.

Benefits of technology

It significantly improves the kinetic performance and interface stability of lithium-rich manganese-based positive electrode materials, reduces interface side reactions, and improves the energy density and cycle life of all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a lithium-rich manganese-based material for an all-solid-state battery as well as a preparation method and application thereof, the preparation method comprises the following steps: mixing and drying a lithium-rich manganese-based carbonate precursor, a dopant and a first solvent to obtain a doped lithium-rich manganese-based carbonate precursor, and then sintering and washing to obtain a pretreated precursor; and carrying out ball milling on the pretreated precursor, mixing with a lithium source, and calcining to obtain the submicron single crystal type lithium-rich manganese-based positive electrode material, and mixing the single crystal type lithium-rich manganese-based positive electrode material, a metal source coating agent and a second solvent, then removing the second solvent, and roasting to obtain the lithium-rich manganese-based material for the all-solid-state battery. According to the preparation method disclosed by the invention, through internal doping of rare earth ions, design of a submicron single crystal structure and surface in-situ coating, the migration speed of lithium ions and the stability of the crystal structure can be improved, side reactions of an interface are reduced, and the stability of the interface is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries and relates to a lithium-rich manganese-based material for all-solid-state batteries and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the characteristics of high energy density and long cycle life. As an important way of energy storage and supply, they are widely used in various fields. It is worth noting that since the commercialization of lithium-ion batteries, traditional liquid lithium-ion batteries have developed rapidly, but due to the extremely flammable, leaky and corrosive characteristics of organic electrolytes, liquid lithium batteries have serious safety hazards. However, the use of all-solid-state lithium-ion batteries shows great potential in promoting energy density, improving safety and stability.

[0003] In recent years, lithium-rich manganese-based cathode materials have attracted much attention due to their reversible redox of anions, high energy density (>250Wh / kg) and high specific capacity (>300mAh / g), and are regarded as one of the most promising cathode materials in the field of next-generation lithium-ion batteries. Among them, the non-toxicity and high crustal abundance (~950ppm) of the Mn element make lithium-rich manganese-based cathode materials also environmentally friendly and low-cost. In addition, there are serious bottlenecks in the performance of oxygen release, metal ion dissolution and phase change of lithium-rich manganese-based cathode materials in liquid lithium-ion batteries. However, all-solid-state lithium-ion batteries composed of high-capacity lithium-rich manganese-based cathode materials, lithium negative electrodes and solid electrolytes are expected to achieve high energy density, safety and cycle life. Therefore, the application of lithium-rich manganese-based cathode materials in all-solid-state lithium-ion batteries has become a promising direction for the development of all-solid-state lithium-ion batteries with high energy density and safety.

[0004] Therefore, lithium-rich manganese-based positive electrode materials have significant advantages such as high energy density, low cost and environmental friendliness, and are expected to match high specific capacity / high voltage positive electrodes and metallic lithium negative electrodes for stable operation. Compared with the currently commercialized positive electrode materials, it has huge room for improvement in energy density, safety, stability and other aspects. In addition, the application of lithium-rich manganese-based positive electrode materials in all-solid-state lithium batteries can further improve the safety and stability of the battery system. However, in all-solid-state batteries, the use of high-capacity lithium-rich manganese-based positive electrode materials has been limited by slow kinetics and serious interface problems, including slow diffusion of lithium ions at the interface between the bulk and lithium-rich manganese-based positive electrode material particles, slow kinetics of anion redox reactions, and serious interface side reactions between lithium-rich manganese-based positive electrode material particles and solid electrolytes.

[0005] That is, although the application of lithium-rich manganese-based positive electrode materials in all-solid-state lithium batteries can further improve their safety and stability, they still face serious kinetic and interface problems during the application process, which hinders the full utilization of anion redox and limits the capacity performance of lithium-rich manganese-based positive electrode materials. It will also lead to structural degradation of the positive electrode material and damage the solid electrolyte, thereby hindering the diffusion of Li ions at the interface, and then hindering the redox kinetics of anions.

[0006] Based on the above research, it is necessary to provide a method for preparing a lithium-rich manganese-based positive electrode material. The lithium-rich manganese-based positive electrode material obtained by the preparation method has excellent kinetic properties and high interface stability. Summary of the invention

[0007] The purpose of the present invention is to provide a lithium-rich manganese-based material for all-solid-state batteries, a preparation method and an application thereof. The preparation method can improve the lithium ion migration speed and the stability of the crystal structure, reduce interface side reactions, and improve interface stability through internal doping of rare earth ions, design of submicron single crystal structure and in-situ surface coating, thereby overcoming the problems of slow kinetics and serious interface side reactions of lithium-rich manganese-based positive electrode materials in all-solid-state batteries.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a lithium-rich manganese-based material for an all-solid-state battery, the preparation method comprising the following steps:

[0010] (1) mixing and drying a lithium-rich manganese-based carbonate precursor, a dopant and a first solvent to obtain a doped lithium-rich manganese-based carbonate precursor; the dopant includes an ion radius greater than Mn 4+ trivalent rare earth ions;

[0011] (2) sintering and washing the doped lithium-rich manganese-based carbonate precursor described in step (1) to obtain a pretreated precursor;

[0012] (3) ball-milling the pretreated precursor in step (2), mixing with a lithium source and calcining to obtain a submicron single crystal lithium-rich manganese-based positive electrode material;

[0013] (4) Mixing the single crystal lithium-manganese-rich positive electrode material, the metal source coating agent and the second solvent described in step (3), then removing the second solvent and calcining to obtain the lithium-manganese-rich material for an all-solid-state battery.

[0014] The present invention first mixes and dries a lithium-rich manganese-based carbonate precursor, a dopant and a first solvent, and then dopes the lithium-rich manganese-based carbonate precursor with rare earth elements. Compared with doping during the preparation of the lithium-rich manganese-based carbonate precursor by co-precipitation, the problem of element segregation caused by different precipitation coefficients of different metal ions is avoided; secondly, according to the doping method of the present invention, the doping element is not easy to diffuse into the interior of the material, and may also be distributed on the surface of the precursor to affect subsequent coating. Therefore, after doping, the present invention first sintered the doped lithium-rich manganese-based carbonate precursor to allow the doping element to fully diffuse into the interior of the precursor, and then washed to remove the doping element on the surface, and then performed the preparation of submicron single crystal lithium-rich manganese-based positive electrode material in step (3) and the coating step in step (4); furthermore, the present invention adopts an in-situ coating method to coat the fast ion conductor, which can be coordinated with the above steps to obtain a uniform coating layer, and finally obtain a modified lithium-rich manganese-based positive electrode material with rare earth elements doped inside and fast ion conductor coated outside.

[0015] The modified lithium-rich manganese-based positive electrode material of the present invention is doped with rare earth ions, wherein the ionic radius of the rare earth ions when positive trivalent is larger than that of Mn 4+ radius, making large ionic radius rare earth ions such as Y 3+ Successfully replaced Mn with a smaller ionic radius 4+ , so that the lithium ion diffusion channel of the lithium-rich manganese-based positive electrode material is expanded, which is beneficial to the rapid migration of lithium ions; then, the present invention enhances the solid-solid contact between the positive electrode and SE in the all-solid-state battery through the design of the single crystal structure of the lithium-rich manganese-based positive electrode material, shortens the transport path of ions and electrons in the positive electrode particles, and thus improves the kinetic performance of the positive electrode; finally, the present invention constructs a fast ion conductor coating layer, further improves the transmission capacity of Li ions at the interface, slows down the oxygen release and spinel phase transition on the surface, and significantly improves the structural stability of the lithium-rich manganese-based positive electrode material; in addition, the protective effect of the coating layer further reduces the contact between the highly active surface oxygen of the lithium-rich manganese-based material and SE, effectively reduces the interface side reactions, and effectively improves the interface stability and cyclability of the material.

[0016] Preferably, the dopant in step (1) comprises yttrium salt and / or cerium salt.

[0017] The present invention preferably dopes Y, and Y element doping can form stronger YO, which improves the stability of the internal crystal structure of the material and reduces the contact between the highly active surface oxygen of the lithium-rich manganese-based positive electrode material and SE.

[0018] Preferably, in the doped lithium-rich manganese-based carbonate precursor in step (1), the content of the doping element is 0-3wt%, but does not include 0wt%. For example, it can be 0.5wt%, 1wt%, 2wt% or 3wt%, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 1-3wt%.

[0019] Preferably, in step (1), the first solvent comprises an alcohol solvent, and the alcohol solvent comprises ethanol.

[0020] Preferably, the method for preparing the lithium-rich manganese-based carbonate precursor in step (1) comprises the following steps:

[0021] The nickel-cobalt-manganese metal salt solution, the carbonate precipitant solution and the complexing agent solution are subjected to a coprecipitation reaction to obtain the lithium-rich manganese-based carbonate precursor.

[0022] Preferably, in the nickel-cobalt-manganese metal salt solution, the molar ratio of nickel ions, cobalt ions and manganese ions is (0.1-0.25):(0.1-0.25):(0.4-0.6), for example, it can be 0.1:0.2:0.5, 0.2:0.2:0.4 or 0.25:0.25:0.6, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] Preferably, the pH of the coprecipitation reaction is 7.5-8.5, for example, 7.5, 8 or 8.5, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0024] Preferably, after the coprecipitation reaction is completed, filtering, washing, drying and grinding are further performed.

[0025] Preferably, the sintering temperature in step (2) is 250-450°C, for example, 250°C, 300°C, 400°C or 450°C, and the sintering time is 3-5h, for example, 3h, 4h or 5h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] In step (2) of the present invention, preliminary sintering is performed at a low temperature to allow the doping elements to fully diffuse into the interior of the precursor. The sintering temperature is preferably within the above range. If the sintering temperature is too low, it is not conducive to the diffusion of the doping elements. If the sintering temperature is too high, it affects the subsequent preparation of single-crystal lithium-manganese-rich positive electrode materials.

[0027] Preferably, the washing liquid used in step (2) comprises an alcohol solvent.

[0028] Preferably, the alcohol solvent includes ethanol.

[0029] Preferably, when the pretreated precursor in step (2) is ball-milled and then mixed with the lithium source, a molten salt is also added.

[0030] Preferably, the molten salt comprises NaCl.

[0031] Preferably, the mass ratio of the lithium source and the molten salt in step (3) is 1:(0.5-2), for example, it can be 1:1:0.5, 1:1, 1:1.5 or 1:2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the calcination in step (3) includes first calcining at 400-600°C, for example, 400°C, 500°C or 600°C, for 4-6h, for example, 4h, 5h or 6h, and then continuing to heat up to 800-900°C, for example, 800°C, 850°C or 900°C, and calcining for a second time for 10-14h, for example, 10h, 12h or 14h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0033] Preferably, the pretreated precursor in step (2) is first ball-milled and then mixed with a lithium source and calcined, and after the calcination in step (3), it is also washed, dried and heat-treated to obtain a submicron single crystal lithium-rich manganese-based positive electrode material.

[0034] The present invention carries out calcination in the presence of molten salt, and after calcination, it also carries out water washing, drying and heat treatment, so as to form a submicron single crystal lithium-manganese-rich positive electrode material. The design of the submicron single crystal structure can enhance the solid-solid contact between the cathode and the solid electrolyte (SE) in the all-solid-state battery, shorten the transport path of ions and electrons in the positive electrode particles, and improve the kinetic performance of the lithium-manganese-rich positive electrode material.

[0035] Preferably, the drying temperature is 110-130°C, such as 110°C, 120°C or 130°C, and the drying time is 3-5h, such as 3h, 4h or 5h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, the heat treatment temperature is 400-500°C, for example, 400°C, 450°C or 500°C, and the time is 4-6h, for example, 4h, 5h or 6h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the metal source coating agent in step (4) comprises a molybdenum source.

[0038] Preferably, the molybdenum source comprises (NH4)6Mo7O 24 ·H2O.

[0039] Preferably, in step (4), the second solvent comprises deionized water.

[0040] Preferably, the method of removing the second solvent in step (4) includes evaporating at 110-130°C, for example, 110°C, 120°C or 130°C, for 3-5h, for example, 3h, 4h or 5h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] Preferably, the calcination in step (4) comprises first calcining at 250-350°C, for example, 250°C, 300°C or 350°C, for 1.5-2.5h, for example, 1.5h, 2h or 2.5h, and then calcining at 600-800°C, for example, 600°C, 700°C or 800°C, for 8-12h, for example, 8h, 10h or 12h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0042] In a second aspect, the present invention provides a lithium-rich manganese-based material for an all-solid-state battery, wherein the lithium-rich manganese-based material for an all-solid-state battery is prepared by the preparation method described in the first aspect;

[0043] The lithium-rich manganese-based material for an all-solid-state battery comprises a core and a coating layer on the surface of the core, the core is doped with a rare earth element, and the coating layer comprises a fast ion conductor.

[0044] In a third aspect, the present invention provides an all-solid-state battery, comprising the lithium-rich manganese-based material for an all-solid-state battery as described in the second aspect.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] (1) The rare earth elements of the present invention are doped into the lithium-rich manganese-based precursor, which can expand the lithium ion diffusion channel of the lithium-rich manganese-based material, facilitate the rapid migration of lithium ions, and form stronger rare earth-O bonds, thereby improving the stability of the internal crystal structure of the material.

[0047] (2) The design of the submicron single crystal structure of the present invention can enhance the solid-solid contact between the positive electrode and the solid electrolyte in the all-solid-state battery, shorten the transport path of ions and electrons in the positive electrode material particles, and improve the kinetic performance of the lithium-rich manganese-based positive electrode material.

[0048] (3) The present invention constructs a coating layer by adopting an in-situ coating method, such as constructing a Li2MoO4 coating layer, which further enhances the transport capacity of Li ions at the interface and reduces the contact between the highly active surface oxygen of the lithium-rich manganese-based material and SE, effectively reducing the interface side reactions and further improving the interface stability. DETAILED DESCRIPTION

[0049] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0050] Example 1

[0051] This embodiment provides a method for preparing a lithium-rich manganese-based material for an all-solid-state battery, the preparation method comprising the following steps:

[0052] (1) NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O with a Ni:Co:Mn molar ratio of 0.13:0.13:0.54 were dissolved in deionized water to obtain an aqueous solution with a concentration of 2.0 mol / L, which was added to a continuous stirring reactor and the temperature was maintained at 60°C. In addition, a Na2CO3 aqueous solution (containing a 0.4 mol / L NH3·H2O aqueous solution) with a concentration of 2.0 mol / L was prepared in another container.

[0053] Under the action of the stirrer, the above two solutions are slowly and continuously added to the reactor at a certain rate by a peristaltic pump to react, so that they are fully precipitated and crystallized. The pH of the reaction process is maintained at 8. After a period of reaction, the coprecipitated particles are filtered, washed, dried at 120° C. for 6 hours and ground to obtain a carbonate precursor;

[0054] (2) adding the carbonate precursor described in step (2) to the ethanol solution and dispersing it by ultrasonication, then adding 2 wt% Y(NO3)3·6H2O to the solution, stirring vigorously for 3 h to completely disperse it, and then drying to obtain a doped lithium-rich manganese-based carbonate precursor;

[0055] (3) sintering the doped lithium-rich manganese-based carbonate precursor at 300° C. for 4 h, washing with ethanol and sintering the obtained sintered material after cooling, and drying to obtain a pretreated precursor;

[0056] (4) The pretreated precursor of step (3) was first ball-milled in an ethanol solution at a rate of 400 r / min for 2 h, and then uniformly mixed with Li2CO3 (5% excess lithium to compensate for lithium loss during calcination) and NaCl (the mass ratio of Li2CO3 to NaCl was 1:1), and first heated at 500°C for 5 h, and then heated at 850°C for 12 h, wherein the heating rate was 5°C / min;

[0057] (5) After the material in step (4) is naturally cooled to room temperature, it is washed with distilled water several times and dried at 120° C. for 4 h. The dried material is calcined at 450° C. at a heating rate of 5° C. / min for 5 h to obtain a submicron single crystal lithium-rich manganese-based positive electrode material;

[0058] (6) Take (NH4)6Mo7O 24 ·H2O is dissolved in deionized water, and then the single crystal lithium-rich manganese-based positive electrode material of step (5) is added (wherein the molar ratio of Mo element to the single crystal lithium-rich manganese-based positive electrode material is 2%), ultrasonicated for 30 minutes and then evaporated at 120°C for 4 hours, and finally the material is calcined at 300°C for 2 hours, and then calcined at 700°C for 10 hours, wherein the heating rate is 5°C / min, and finally the lithium-rich manganese-based material for an all-solid-state battery is obtained, wherein the modified lithium-rich manganese-based positive electrode material of the all-solid-state battery is doped with Y and the surface is coated with Li2MoO4.

[0059] Example 2

[0060] This embodiment provides a method for preparing a lithium-rich manganese-based material for an all-solid-state battery, the preparation method comprising the following steps:

[0061] (1) NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O with a Ni:Co:Mn molar ratio of 0.13:0.13:0.54 were dissolved in deionized water to obtain an aqueous solution with a concentration of 2.0 mol / L, which was added to a continuous stirring reactor and the temperature was maintained at 60°C. In addition, a Na2CO3 aqueous solution (containing a 0.4 mol / L NH3·H2O aqueous solution) with a concentration of 2.0 mol / L was prepared in another container.

[0062] Under the action of the stirrer, the above two solutions are slowly and continuously added to the reactor at a certain rate by a peristaltic pump to react, so that they are fully precipitated and crystallized. The pH of the reaction process is maintained at 8. After a period of reaction, the coprecipitated particles are filtered, washed, dried at 120° C. for 6 hours and ground to obtain a carbonate precursor;

[0063] (2) adding the carbonate precursor described in step (2) to the ethanol solution and dispersing it by ultrasonication, then adding 1 wt% Y(NO3)3·6H2O to the solution, stirring vigorously for 3 h to completely disperse it, and then drying to obtain a doped lithium-rich manganese-based carbonate precursor;

[0064] (3) sintering the doped lithium-rich manganese-based carbonate precursor at 450° C. for 3 h, washing the sintered material with ethanol after cooling, and drying to obtain a pretreated precursor;

[0065] (4) The pretreated precursor of step (3) was first ball-milled in an ethanol solution at a rate of 400 r / min for 2 h, and then uniformly mixed with Li2CO3 (5% excess lithium to compensate for lithium loss during calcination) and NaCl (the mass ratio of Li2CO3 to NaCl was 1:0.5), and first heated at 600°C for 6 h, and then heated at 800°C for 10 h, wherein the heating rate was 5°C / min;

[0066] (5) After the material in step (4) is naturally cooled to room temperature, it is washed with distilled water several times and dried at 110° C. for 5 h. The dried material is calcined at 500° C. at a heating rate of 5° C. / min for 4 h to obtain a submicron single crystal lithium-rich manganese-based positive electrode material;

[0067] (6) Take (NH4)6Mo7O 24 ·H2O is dissolved in deionized water, and then the single crystal lithium-rich manganese-based positive electrode material of step (5) is added (wherein the molar ratio of Mo element to the single crystal lithium-rich manganese-based positive electrode material is 2%), ultrasonicated for 30 minutes and then evaporated at 110°C for 5 hours, and finally the material is calcined at 350°C for 1.5 hours, and then calcined at 600°C for 12 hours, wherein the heating rate is 5°C / min, and finally the lithium-rich manganese-based material for an all-solid-state battery is obtained, wherein the modified lithium-rich manganese-based positive electrode material of the all-solid-state battery is doped with Y and the surface is coated with Li2MoO4.

[0068] Example 3

[0069] This embodiment provides a method for preparing a lithium-rich manganese-based material for an all-solid-state battery, the preparation method comprising the following steps:

[0070] (1) NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O with a Ni:Co:Mn molar ratio of 0.13:0.13:0.54 were dissolved in deionized water to obtain an aqueous solution with a concentration of 2.0 mol / L, which was added to a continuous stirring reactor and the temperature was maintained at 60°C. In addition, a Na2CO3 aqueous solution (containing a 0.4 mol / L NH3·H2O aqueous solution) with a concentration of 2.0 mol / L was prepared in another container.

[0071] Under the action of the stirrer, the above two solutions are slowly and continuously added to the reactor at a certain rate by a peristaltic pump to react, so that they are fully precipitated and crystallized. The pH of the reaction process is maintained at 8. After a period of reaction, the coprecipitated particles are filtered, washed, dried at 120° C. for 6 hours and ground to obtain a carbonate precursor;

[0072] (2) adding the carbonate precursor described in step (2) to the ethanol solution and dispersing it by ultrasonication, then adding 3 wt % Y(NO3)3·6H2O to the solution, stirring vigorously for 3 h to completely disperse it, and then drying to obtain a doped lithium-rich manganese-based carbonate precursor;

[0073] (3) sintering the doped lithium-rich manganese-based carbonate precursor at 250° C. for 5 h, washing the sintered material with ethanol after cooling, and drying to obtain a pretreated precursor;

[0074] (4) The pretreated precursor of step (3) was first ball-milled in an ethanol solution at a rate of 400 r / min for 2 h, and then uniformly mixed with Li2CO3 (5% excess lithium to compensate for lithium loss during calcination) and NaCl (the mass ratio of Li2CO3 to NaCl was 1:2), and first heated at 400°C for 4 h, and then heated at 900°C for 14 h, wherein the heating rate was 5°C / min;

[0075] (5) After the material in step (4) is naturally cooled to room temperature, it is washed with distilled water several times and dried at 130° C. for 3 h. The dried material is calcined at 400° C. at a heating rate of 5° C. / min for 6 h to obtain a submicron single crystal lithium-rich manganese-based positive electrode material;

[0076] (6) Take (NH4)6Mo7O 24·H2O is dissolved in deionized water, and then the single crystal lithium-rich manganese-based positive electrode material of step (5) is added (wherein the molar ratio of Mo element to the single crystal lithium-rich manganese-based positive electrode material is 2%), ultrasonicated for 30 minutes and then evaporated at 130°C for 3 hours, and finally the material is calcined at 250°C for 2.5 hours, and then calcined at 800°C for 8 hours, wherein the heating rate is 5°C / min, and finally the lithium-rich manganese-based material for an all-solid-state battery is obtained, wherein the modified lithium-rich manganese-based positive electrode material of the all-solid-state battery is doped with Y and the surface is coated with Li2MoO4.

[0077] Example 4

[0078] This embodiment provides a method for preparing a lithium-rich manganese-based material for an all-solid-state battery. The preparation method is the same as that of Embodiment 1 except that the sintering temperature in step (3) is 200°C.

[0079] Example 5

[0080] This embodiment provides a method for preparing a lithium-rich manganese-based material for an all-solid-state battery. The preparation method is the same as that of Embodiment 1 except that the sintering temperature in step (3) is 500°C.

[0081] Example 6

[0082] This embodiment provides a method for preparing a lithium-rich manganese-based material for an all-solid-state battery. The preparation method is the same as that of Embodiment 1 except that in step (2), 0.5 wt% Y(NO3)3·6H2O is added as a doping amount.

[0083] Example 7

[0084] This embodiment provides a method for preparing a lithium-rich manganese-based material for an all-solid-state battery. The preparation method is the same as that of Embodiment 1 except that in step (3), 3.5 wt% of Y(NO3)3·6H2O is added as a doping amount.

[0085] Comparative Example 1

[0086] This comparative example provides a method for preparing a lithium-rich manganese-based material for an all-solid-state battery. The preparation method is the same as Example 1 except that step (3) is not performed.

[0087] Comparative Example 2

[0088] This comparative example provides a method for preparing a lithium-rich manganese-based material for an all-solid-state battery. The preparation method is the same as Example 1 except that step (2) and step (3) are not performed.

[0089] Comparative Example 3

[0090] This comparative example provides a method for preparing a lithium-rich manganese-based material for an all-solid-state battery. The preparation method is the same as Example 1 except that step (6) is not performed.

[0091] Comparative Example 4

[0092] This embodiment provides a method for preparing a lithium-rich manganese-based material for an all-solid-state battery. The preparation method is the same as that of Embodiment 1 except that the ball milling described in step (4) and step (5) are not performed.

[0093] The modified lithium-rich manganese-based positive electrode material of the all-solid-state battery obtained in the above embodiments and comparative examples was prepared into a positive electrode sheet, and then prepared into an all-solid-state battery with a LiIn negative electrode and a Li6PS5Cl electrolyte sheet. The electrochemical performance and cycle performance of the all-solid-state battery were tested under the conditions of a voltage of 2.0-4.8V and a charge and discharge rate of 0.1C.

[0094] The test results are shown in the following table:

[0095] Table 1

[0096] First discharge specific capacity (mAh / g) 300-cycle capacity retention rate (%) Example 1 288.7 89.3 Example 2 289.1 86.6 Example 3 287.9 82.1 Example 4 279.7 80.7 Example 5 268.3 79.2 Example 6 280.9 88.3 Example 7 278.2 83.6 Comparative Example 1 279.9 85.6 Comparative Example 2 277.8 74.2 Comparative Example 3 281.5 78.1 Comparative Example 4 286.6 81.6

[0097] From the above table we can see that:

[0098] It can be seen from Example 1 and Comparative Example 1 that after doping, the present invention also performs sintering and washing steps, which can promote the diffusion of doping elements into the interior, remove the doping elements on the surface of the precursor, promote the subsequent coating step, and improve the uniformity of the coating layer, thereby further improving the performance of the all-solid-state battery; It can be seen from Example 1 and Comparative Example 2 that the present invention can improve the migration speed of lithium ions and the stability of the material by doping, thereby improving the performance of the all-solid-state battery; It can be seen from Example 1 and Comparative Example 3 that the setting of the coating layer of the present invention can reduce the interface reaction, improve the transmission capacity of lithium ions on the surface of the material, and improve the performance of the material; It can be seen from Example 1 and Examples 4-5 that after doping, the present invention first sinters the precursor, which can promote the diffusion of doping elements, and the sintering temperature will affect the stability of the material and the subsequent preparation process, thereby further affecting the performance of the all-solid-state battery; It can be seen from Example 1 and Examples 6-7 that the content of the doping element of the present invention will also affect the lithium ion transmission speed and stability, etc., thereby affecting the performance of the all-solid-state battery; It can be seen from Example 1 and Comparative Example 4 that when preparing the positive electrode material, the design of the submicron single crystal structure of the present invention is conducive to improving the performance of the all-solid-state battery.

[0099] In summary, the present invention provides a lithium-rich manganese-based material for all-solid-state batteries, a preparation method and an application thereof. The preparation method can improve the lithium ion migration speed and the stability of the crystal structure, reduce interfacial side reactions, and improve interface stability through internal doping of rare earth ions, design of submicron single crystal structure and in-situ surface coating, thereby overcoming the problems of slow kinetics and serious interfacial side reactions of lithium-rich manganese-based positive electrode materials in all-solid-state batteries.

[0100] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a lithium-rich manganese-based material for an all-solid-state battery, characterized in that: The preparation method comprises the following steps: (1) mixing and drying a lithium-rich manganese-based carbonate precursor, a dopant and a first solvent to obtain a doped lithium-rich manganese-based carbonate precursor; the dopant includes an ion radius greater than Mn 4+ trivalent rare earth ions; (2) sintering and washing the doped lithium-rich manganese-based carbonate precursor described in step (1) to obtain a pretreated precursor; (3) ball-milling the pretreated precursor in step (2), mixing with a lithium source and calcining to obtain a submicron single crystal lithium-rich manganese-based positive electrode material; (4) Mixing the single crystal lithium-manganese-rich positive electrode material, the metal source coating agent and the second solvent described in step (3), then removing the second solvent and calcining to obtain the lithium-manganese-rich material for an all-solid-state battery.

2. The preparation method according to claim 1, characterized in that: Step (1) The dopant comprises yttrium salt and / or cerium salt; Preferably, in the doped lithium-rich manganese-based carbonate precursor in step (1), the content of the doping element is 0-3wt%, but excluding 0wt%, and preferably 1-3wt%; Preferably, in step (1), the first solvent comprises an alcohol solvent.

3. The preparation method according to claim 1 or 2, characterized in that: The method for preparing the lithium-rich manganese-based carbonate precursor in step (1) comprises the following steps: The nickel-cobalt-manganese metal salt solution, the carbonate precipitant solution and the complexing agent solution are subjected to a coprecipitation reaction to obtain the lithium-rich manganese-based carbonate precursor.

4. The preparation method according to claim 3, characterized in that: In the nickel-cobalt-manganese metal salt solution, the molar ratio of nickel ion, cobalt ion and manganese ion is (0.1-0.25):(0.1-0.25):(0.4-0.6); Preferably, the pH of the coprecipitation reaction is 7.5-8.5; Preferably, after the coprecipitation reaction is completed, filtering, washing, drying and grinding are further performed.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The sintering temperature in step (2) is 250-450° C. and the sintering time is 3-5 h; Preferably, the washing liquid used in step (2) comprises an alcohol solvent.

6. The preparation method according to any one of claims 1 to 5, characterized in that: When the pretreated precursor in step (2) is ball-milled and mixed with the lithium source, a molten salt is also added; Preferably, the molten salt comprises NaCl; Preferably, the mass ratio of the lithium source to the molten salt in step (3) is 1:(0.5-2); Preferably, the calcination in step (3) includes first calcining at 400-600°C for 4-6 hours, and then continuing to heat up to 800-900°C for a second calcination for 10-14 hours.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The pretreated precursor of step (2) is first ball-milled and then mixed with a lithium source and calcined, and after the calcination of step (3), it is also washed, dried and heat-treated to obtain a submicron single crystal lithium-rich manganese-based positive electrode material; Preferably, the drying temperature is 110-130°C and the drying time is 3-5h; Preferably, the heat treatment is carried out at a temperature of 400-500° C. and for a time of 4-6 hours.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The metal source coating agent in step (4) comprises a molybdenum source; Preferably, the molybdenum source comprises (NH4)6Mo7O 24 ·H2O; Preferably, the second solvent in step (4) comprises deionized water; Preferably, the method of removing the second solvent in step (4) comprises evaporating at 110-130° C. for 3-5 hours; Preferably, the calcination in step (4) comprises a primary calcination at 250-350°C for 1.5-2.5h, and a secondary calcination at 600-800°C for 8-12h.

9. A lithium-rich manganese-based material for an all-solid-state battery, characterized in that: The lithium-rich manganese-based material for the all-solid-state battery is prepared by the preparation method according to any one of claims 1 to 8; The lithium-rich manganese-based material for an all-solid-state battery comprises a core and a coating layer on the surface of the core, the core is doped with a rare earth element, and the coating layer comprises a fast ion conductor.

10. An all-solid-state battery, characterized in that: The all-solid-state battery comprises the lithium-rich manganese-based material for an all-solid-state battery as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation and doping modification method of single crystal lithium nickel cobalt aluminate positive electrode material

    CN111646520A

  • Modification method of single-crystal ternary positive electrode material

    CN112080800A

  • Composite in-situ coated high-nickel single-crystal positive electrode material and preparation method thereof

    CN115571927A

  • Preparation method of NCM ternary positive electrode material for improving uniformity and conductivity of coating layer

    CN115692631A

  • Cobalt-free single-crystal positive electrode material and preparation method thereof, and lithium ion battery

    CN117117109A

Cited By

  • Composite positive electrode material and preparation method and application thereof

    CN120376624A

  • Doped lithium-rich manganese-based positive electrode material and preparation method thereof

    CN121331815A

  • Lithium-rich manganese-based material for solid-state battery as well as preparation method and application of lithium-rich manganese-based material

    CN121377135A